Saint Anne’s Church in Mazagaon - Mumbai Archive Project Team (Jio Institute, 2024)
Drawing inspiration from the classic Gothic architectural era, Saint Anne’s Church in Mazagaon features pointed arches, ribbed vaults, and lofty spires, which are all hallmarks of the neo-Gothic style. The foundation stone was laid on April 10, 1880, and the Church was consecrated on November 6, 1881, by Bishop Leo Meurin.